2001
DOI: 10.1002/jsfa.843
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds in Bacillus‐fermented soybeans

Abstract: Thua nao, a traditional, proteolytic, fermented soybean condiment of northern Thailand, was prepared from cooked whole soybeans by natural¯ora fermentation. The microbial¯ora during the fermentation was dominated by Bacillus species. The formation of volatile compounds during the fermentation was studied. In addition, the volatile compounds of two samples of commercial dried thua nao and two samples of commercial Japanese natto were analysed. Fermentation led to a large increase in the concentration of total v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 18 publications
4
84
2
2
Order By: Relevance
“…Many authors have reported that controlled fermentation of African locust beans or soybeans led to an enormous increase in the concentration of volatile compounds, due to the metabolic activities of the bacteria involved, particularly when using a pure culture of microorganisms. 11,13,24 The B. subtilis strains were found to produce a diversity of hydrolases including several proteases and lipases. 15,29 These hydrolases are particularly more active during controlled fermentation and contribute significantly to the flavour and aroma-generating reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have reported that controlled fermentation of African locust beans or soybeans led to an enormous increase in the concentration of volatile compounds, due to the metabolic activities of the bacteria involved, particularly when using a pure culture of microorganisms. 11,13,24 The B. subtilis strains were found to produce a diversity of hydrolases including several proteases and lipases. 15,29 These hydrolases are particularly more active during controlled fermentation and contribute significantly to the flavour and aroma-generating reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial activity during fermentation of soybeans which is linked to extra cellular hydrolase enzymes including amylase, proteases, lipases and sucrose is mostly responsible for the change in volatile compounds, contributing the typical flavour. Leejeerajumnean et al, (2001) reported a significant increase in concentration of volatile compounds, up to 100times in concentration, during fermentation of cooked soybeans within 72 hours. The major components of these volatiles are 3-hydroxybutanone (acetoin), 2-methylbutanoic acid, pyrazines, and dimethyl sulfides together with other aromatic compounds.…”
Section: Aromatic Compounds and Flavouring Agentsmentioning
confidence: 99%
“…Pyrazine class is unique and has been reported to contribute to the roasted feature of the food products (Maga 1992). In addition, pyrazines are also commonly found in the fermented soybean products (Sugawara et al, 1998;Leejeerajumnean et al, 2001;Dajanta et al, 2011). The presence of these pyrazines is related to sensory attributes as a flavourable odour (i.e., nutty and roasted odour) (Lee and Ahn, 2009).…”
Section: Pyrazinesmentioning
confidence: 99%
“…Published by Rynnye Lyan Resources researchers have paid their attention to work on this issue. Numerous reports have described the volatile components in the fermented soybean products; these include Korean Chungkukjang (Tanaka et al, 1998), Natto (Sugawara et al, 1998), and Thua Nao (Leejeerajumnean et al, 2001;Dajanta et al, 2011). Although these studies have shown that the frequent compounds in the fermented soybean products include esters, acids, pyrazines, and phenolic compounds, it should be noted that there are variations of the volatile component profiles among these fermented soybeans mainly depending on the soybean variety, microflora involved, and the processing conditions (Tanaka et al, 1998;Leejeerajumnean et al, 2001).…”
Section: Introductionmentioning
confidence: 99%